PARTISIPASI DESA WISATA NGLANGGERAN YOGYAKARTA DALAM “BEST TOURISM VILLAGES” PADA UNITED NATION WORLD TOURISM ORGANIZATION (UNWTO) TAHUN 2021 - Bella, Fatma; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Nglanggeran Tourism Village is one of the villages in Yogyakarta that has been nominated for "Best Tourism Villages" organized by the United Nation World Tourism Organization (UNWTO) in 2021. In participating in "Best Tourism Villages" Nglanggeran Tourism Village was recommended by the Ministry of Tourism and Creative Economy and contacted the GunungKidul Tourism Office to arrange for the Nglanggeran Tourism Village to register as a participant in the "Best Tourism Villages". This qualitative research asks about the Paradiplomacy of the Nglanggeran Tourism Village in the international arena. To answer this question, data is needed from journals, news, direct interviews and official documents. Researchers use paradiplomacy theory to analyze data and obtain results. This research shows that the Nglanggeran Tourism Village uses paradiplomacy to take part in the international world. The strategy carried out by the Nglanggeran Tourism Village to participate in the "Best Tourism Villages" beat two other representatives, the Wae Rebo Tourism Village, NTT and the Tetebatu Tourism Village, NTB, due to the multidisciplinary and innovative development criteria for the Nglanggeran Tourism Village in accordance with the Sustainable Development Goals (SDGs). The participation of these villages is a recommendation from the Ministry of Tourism and Creative Economy as the central government which contributes with the department regional tourism as local government and involving community groups to form paradiplomacy which proves that autonomous regions cannot take part in the international arena independently without any attachment to the central government. Keywords : Nglanggeran Tourism Village, Best Tourism Villages, UNWTO, Paradiplomacy, SDGs.